Distance Sensitivity of Export: A Firm-Product Level Approach - Viroj Jienwatcharamongkhol (Lund University, School of Economics and Management, Department of Economics, 2012)
Recent literature suggests that product characteristics assert different distance sensitivity on trade flows. But the empirical evidences still find conflicting results. Previous studies have examined the effect of distance on the export decisions across different product groups at the aggregate level. In this paper the analyses are executed at a disaggregated firm-product level to examine the issue based on individual firm's decisions. Empirically, I employ a gravity model on Swedish micro-level export data in the manufacturing sector. The results suggest that homogeneous products are more sensitive to distance than differentiated products for the export selection and are insignificant for the export intensity.
Keywords: F12; F14; F41; 330; distance sensitivity; export decisions; gravity model; micro-data